Investigating the Effect of Methamphetamine Toxicity on Mesenchymal Stem Cells Derived from Adipose Tissue in Rats - Fariba Jafari Shibani; Seyyed Ebrahim Hosseini; Davood Mehrabani (Fasa University of Medical Sciences, 2020)
Background & Objective: Methamphetamine is a hallucinogenic and addictive substance that is widely used worldwide. Cellular toxicity in various cells, especially in nerve cells, is one of the reported effects of this psychoactive substance. Therefore, this study aimed to investigate the effect of methamphetamine cytotoxicity on adult mesenchymal stem cells Materials & Methods: In this experimental study, mesenchymal stem cells were extracted from the adipose tissue of adult male rats of the Wistar breed and after culturing, their being mesenchymal was confirmed by flowcytometry method using CD34-RPE, CD90-RPE and CD105-RPE conjugate antibodies. In the third passage of cell culture, the effect of methamphetamine toxicity at a concentration of 0.6 mmol during 1 to 7 days on the growth process of these cells was investigated by MTT test. Results: The cells detached from the adipose tissue were completely adhered to the floor of the flask 24 hours after being transferred to the cell culture flask. The results of flowcytometry showed that the expression of negative endothelial surface marker (CD34) and the expression of mesenchymal cell markers (CD90, CD105) were positive, which confirmed the basic identity of the extracted cells. The results of the MTT test also showed a significant reduction in the growth of cells treated with 0.6 mmol methamphetamine compared with the control group at p <0.05. Conclusion: Cells isolated from adipose tissue are the basic mesenchymal type in which methamphetamine can induce the effects of cell toxicity and inhibit growth.